Population pharmacokinetics of oseltamivir and oseltamivir carboxylate in obese and Non-obese volunteers. - Chairat, K; Jittamala, P; Hanpithakpong, W; Day, N; White, N; Pukrittayakamee, S; Tarning, J (Wiley, 2016)
The aims of this study were to compare the pharmacokinetics of oseltamivir and oseltamivir carboxylate in obese and non-obese individuals and to determine the effect of obesity on the pharmacokinetic properties of oseltamivir and the active antiviral metabolite oseltamivir carboxylate.The population pharmacokinetic properties of oseltamivir and oseltamivir carboxylate were evaluated in 12 obese (body mass index; BMI ≥30 kg/m(2) ) and 12 non-obese (BMI <30 kg/m(2) ) Thai adult volunteers receiving a standard dose of 75 mg and a double dose of 150 mg in a randomised sequence. Concentration-time data were collected and analysed with nonlinear mixed-effects modelling.The pharmacokinetics of oseltamivir and its active metabolite, oseltamivir carboxylate, were described simultaneously by first-order absorption, with a one-compartment disposition model for oseltamivir followed by a metabolism compartment and one-compartment disposition of oseltamivir carboxylate. Creatinine clearance was a significant predictor of oseltamivir carboxylate clearance (3.84% increase for each 10 mL/min increase of creatinine clearance, 95% confidence interval [95% CI] of 0.178 to 8.02%). Obese individuals had an approximately 25% (95% CI of 24% to 28%) higher oseltamivir clearance, 20% higher oseltamivir volume of distribution (95% CI of 19% to 23%) and 10% higher oseltamivir carboxylate clearance (95% CI of 9% to 11%) compared to non-obese individuals. However, these altered pharmacokinetic properties were small and did not change the overall exposure to oseltamivir carboxylate.This confirmed that dose adjustment of oseltamivir in obese individuals was not necessary on a pharmacokinetic basis.